Behavior and Marketing Analysis of Pepper (Piper nigrum L.): A Comparative Study of Farmers, Trading Districts and Retailers in Southeast Sulawesi, Indonesia - Al Zarliani, Wa Ode; Muzuna, Muzuna; Sugianto, Sigit (Caraka Tani: Journal of Sustainable Agriculture, 2023)
Inefficient marketing and low production are the main obstacles in the selling of pepper and they also cause a low bargaining position for farmers in the market. Therefore, this study aims to determine the market behavior activities carried out to determine prices, as well as analyze marketing channels, profits received by participants and efficiency. Samples used in this study were 27 farmers, 4 trading districts, and 3 respondent retailers. The qualitative analysis was used to analyze the pattern of channels, the functions performed by associated agencies and the market behavior of the pepper commodity. Quantitative analysis was also carried out to evaluate the marketing margins, costs incurred by traders, profits received and efficiency. The results show that the selling price of pepper was determined by the merchant, with different payment systems including cash, initial deposit, and balance through oral cooperation in the form of an agreement on a place of sales, followed by the provision of capital to farmers. In the marketing process, 4 patterns of channels were formed, which include local markets and others outside the regency, and their efficiencies were above 50%. These results show that government need to provide pepper markets outside the province to improve the welfare of farmers and ensure they don't depend only on the local marketplace during harvest.